Everyday Citizenship and People with Dementia - Ann-Charlotte, Nedlund (Policy and Practice in Health and Social Care Ser., 2019)
An edited volume discussing the underpinning concepts of citizenship, agency, and participation in the context of the everyday lives of people living with a dementia. The editors explain the theoretical underpinning of citizenship before the contributors show the way it can broaden the everyday lives of people with dementia.